2005
DOI: 10.1016/j.molcel.2005.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Interdomain Communication in the Hsc70 Chaperone

Abstract: Hsp70 family proteins are highly conserved chaperones involved in protein folding, degradation, targeting and translocation, and protein complex remodeling. They are comprised of an N-terminal nucleotide binding domain (NBD) and a C-terminal protein substrate binding domain (SBD). ATP binding to the NBD alters SBD conformation and substrate binding kinetics, but an understanding of the mechanism of interdomain communication has been hampered by the lack of a crystal structure of an intact chaperone. We report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
347
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(370 citation statements)
references
References 47 publications
19
347
1
3
Order By: Relevance
“…The agent of clathrin uncoating is the cytosolic heat-shock cognate protein Hsc70 (Rothman and Schmid 1986). Like all members of the Hsp70 family, Hsc70 has an actin-like ATPase domain linked to a characteristic "molecular clamp" domain, which can capture hydrophobic peptides, exposed on an unfolded polypeptide chain or projecting from an assembly destined for dissociation (Jiang et al 2005). When the enzyme is in the ATP-bound state, the clamp-domain/peptide association is relatively weak, ATP hydrolysis (to ADP and Pi) tightens the clamp, and nucleotide exchange (dissociation of ADP and binding of ATP) opens the clamp, releases the peptide, and completes the cycle.…”
Section: Uncoatingmentioning
confidence: 99%
“…The agent of clathrin uncoating is the cytosolic heat-shock cognate protein Hsc70 (Rothman and Schmid 1986). Like all members of the Hsp70 family, Hsc70 has an actin-like ATPase domain linked to a characteristic "molecular clamp" domain, which can capture hydrophobic peptides, exposed on an unfolded polypeptide chain or projecting from an assembly destined for dissociation (Jiang et al 2005). When the enzyme is in the ATP-bound state, the clamp-domain/peptide association is relatively weak, ATP hydrolysis (to ADP and Pi) tightens the clamp, and nucleotide exchange (dissociation of ADP and binding of ATP) opens the clamp, releases the peptide, and completes the cycle.…”
Section: Uncoatingmentioning
confidence: 99%
“…It was recently demonstrated that dynamic light scattering can be used effectively to monitor clathrin cage disassembly (21,22), thus providing better time resolution than previous studies that were predominantly based on centrifugation and densitometry of SDS-PAGE (19,20). We have further increased the time resolution by which disassembly kinetics can be measured, by monitoring simple perpendicular light scattering using stopped-flow methods to capture events on the milliseconds-to-seconds timescale.…”
mentioning
confidence: 99%
“…In past decades, the entry of JEV into host cells, either mammalian or mosquito, was demonstrated to be significantly influenced by treatment with bafilomycin A1 (Andoh et al, 1998;Nawa, 1998). In fact, a number of flaviviruses like West Nile virus (Jiang et al, 2005), DENV (Acosta et al, 2008) and JEV (Chai et al, 2013), have been known to infect host cells via this pathway. Furthermore, the cationic amphiphilic drug chlorpromazine can interfere with the entry process (Chai et al, 2013;Nawa et al, 2003), revealing that the mode of infection is receptormediated endocytosis and is clathrin-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Hsc70s are highly conserved in structure from prokaryotes to eukaryotes (Boorstein et al, 1994). In general, Hsc70 can be involved in folding/ unfolding and assembly/disassembly of macromolecular structures (Elefant & Palter, 1999;Jiang et al, 2005) as well as anti-apoptotic activity (Powers et al, 2008). Thus, Hsc70 expression is usually beneficial for cells by resisting injury under conditions of minimal stress (Sens et al, 1997).…”
Section: Introductionmentioning
confidence: 99%